Complicated Gastroschisis Is Associated with Greater Intestinal Morbidity than Gastroschisis or Intestinal Atresia Alone - Mutanen, Annika; Koivusalo, Antti; Pakarinen, Mikko (European Journal of Pediatric Surgery, 2018)
Aim The study aimed to compare outcomes and intestinal morbidity among complicated gastroschisis, isolated gastroschisis, and intestinal atresia.Methods In this retrospective observational single institution study, outcomes and intestinal morbidity were compared among gastroschisis complicated by intestinal atresia or perinatal bowel perforation, isolated gastroschisis, and isolated intestinal atresia. We included two cohorts; the first cohort included 68 consecutive patients with complicated gastroschisis (n = 9), isolated gastroschisis (n = 34), and intestinal atresia (n = 25) managed in our center. The second cohort included 20 patients (12 referred) with intestinal failure due to these underlying etiologies managed by our intestinal rehabilitation team.Results Patients with complicated gastroschisis had a significantly longer need for mechanical ventilation, primary hospital stay, and duration of parenteral nutrition (PN) and developed intestinal failure more often compared with other groups (p < 0.05 for all). Reoperations for surgical complications were also more frequent in patients with complicated gastroschisis (p < 0.05). Among those, who developed intestinal failure, autologous intestinal reconstruction (AIR) surgery was performed in 11 patients with comparable frequency in all groups. Repeated AIR surgery for bowel re-dilatation was required in 3/3 patients with complicated gastroschisis and 0/8 with isolated gastroschisis or intestinal atresia (p = 0.004).Conclusion Complicated gastroschisis is associated with markedly increased intestinal morbidity, reflected by prolonged duration of PN, more frequent reoperations for intestinal complications, and bowel re-dilatation after AIR surgery, when compared with patients with isolated gastroschisis or intestinal atresia.
Keywords: intestinal failure; parenteral nutrition; intestinal dysmotility; autologous intestinal reconstruction; serial transverse enteroplasty procedure